Existence and Ulam stability results for nonlinear hybrid implicit Caputo fractional differential equations - Lachouri Adel; Ardjouni Abdelouaheb; Djoudi Ahcene (Mathematica Moravica, 2020)
In this paper, we study the existence, uniqueness and estimate of solutions for nonlinear hybrid implicit Caputo fractional differential equations by using the contraction mapping principle and the generalization of Gronwall's inequality. After that, we also establish the Ulam stability for the problem at hand. Finally, an example is given to illustrate this work.